Application of Functional Data Analysis in Complex Human Movement Analysis - Baifa Zhang; Zhi-Cheng Lin (Quality in Sport)
Functional data analysis, pioneered by Ramsay, the president of the statistical society of Canada, is a novel statistical method widely applied in the field of human movement analysis. This study clarifies the relevant concepts and basic processes of functional data analysis, outlines the computational framework of functional principal component analysis, and focuses on exploring its applications in sports science, clinical rehabilitation, and motor development. Compared to traditional cross-sectional statistics, Functional data nalysis demonstrates unique advantages in human movement analysis research and is expected to become a reliable technical means for exploring the laws of human mechanical movement in the future.